Using photovoice to explore the stress of pre-service teachers in online learning - Kardi Nurhadi; Mega Fariziah Nur Humairoh; Maharani Khansa; Hartia Novianti; Utami Widiati (Studies in English Language and Education, 2025)
The technique of photovoice can be defined as a process whereby people can identify, represent, and enhance their social rules and social practices using photographs accompanied by verbal commentary. The current study uses photovoice to identify and analyze the academic stress experienced by pre-service teachers in an academic reading classroom. This phenomenological case study aims to unravel the stress experienced by undergraduate students while they were engaged in mandatory online learning under pandemic conditions through the use of photovoice. Out of thirty-one students who participated in an online academic reading course, two female students were selected to discuss the photographs they had chosen, reflecting on their lived experiences of mandatory online learning at a private university in West Java, Indonesia. The collection of all the participants data took place from March to June 2020. The data were derived from their photovoice records supplemented by focus group discussion and a follow-up semi-structured interview. The visual illustrations and verbal commentary they produced constitute evidence of pre-service teachers academic stress and provide insights into this phenomenon. The two participants revealed that the possible reasons for academic stress stemmed from the task burden, lack of connection, feelings of loneliness, and exhaustion related to online learning. These results suggest that teacher education programs need to minimize the burden of tasks, give students opportunities to speak about their experiences with online learning and design interactive materials for online learning.